The Influence of E-Marketing on MSME Business Performance in the Culinary Sector and Impact on Customer Loyalty Post the Covid-19 Pandemic in Garut Regency - Hamdani, Nizar Alam; Lindayani, Lindayani; Lestari, Citra Dewi (Entrepreneurship Faculty, Universitas Garut, 2023)
This research aims to analyze the influence of e-marketing on the business performance of Micro, Small and Medium Enterprises (MSMEs) in the culinary sector and its impact on customer loyalty after the COVID-19 pandemic. This type of research is quantitative research with a descriptive approach. The sample used in this research was 100 MSME entrepreneurs in the culinary sector in Garut Regency. Using the Structural Equation Modeling (SEM) method with the help of SmartPLS was used to analyze data from respondents consisting of culinary MSME owners in certain areas. Data obtained through questionnaires are processed and analyzed to test the validity and reliability of the construct, as well as test the proposed hypothesis. The aim of this research is to examine the influence of e-marketing on business performance and its impact on customer loyalty. This research is intended to determine the influence of e-marketing on business performance and the influence of e-marketing on customer loyalty using research that has been conducted previously. The analysis used in this research is the outer model test, inner model test and hypothesis test. The results of this research state that the e-marketing variable has an influence on business performance of 68.8%, which shows that the influence exerted is strong enough to be statistically significant. Then there is the e-marketing variable which has an influence of 68.9% on the customer loyalty variable, which means that the influence exerted is strong enough to be statistically significant. These three variables have a positive influence and are considered capable of influencing e-marketing.